2019
DOI: 10.3390/su11226497
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Relationships between Environmental Performance, E-Government and Corruption: A Multivariate Perspective

Abstract: In order to improve environmental performance, the participation of effective and transparent citizens and governments that help counteract corruption in environmental matters is crucial. In this sense, this work focuses on exploring relationships between e-participation, e-government, the corruption index and environmental performance indicators. To this end, a sample comprising 116 countries from varying geographic regions is used in conjunction with indicators of environmental performance, e-participation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 56 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…Here would be another example of an opportunity to educe AI-Thinking in the analysts. Rather than unquestioningly relying on the counterfactual results produced by the AI-based method, the analysts may like to peruse the work of other sustainability researchers or AI researchers (e.g., see [64][65][66][67][68]), and in turn, ask even more meaningful questions.…”
Section: Predictive Analytics: What If We Want To Achieve High-level mentioning
confidence: 99%
“…Here would be another example of an opportunity to educe AI-Thinking in the analysts. Rather than unquestioningly relying on the counterfactual results produced by the AI-based method, the analysts may like to peruse the work of other sustainability researchers or AI researchers (e.g., see [64][65][66][67][68]), and in turn, ask even more meaningful questions.…”
Section: Predictive Analytics: What If We Want To Achieve High-level mentioning
confidence: 99%
“…In comparison, each node in the cluster is used to gain insight into a bibliometric grouping. That way, corruption is the green color node that dominates the largest circle because the scope of corruption often occurs in the internal area of global government and is often associated with several government issues (Rodríguez-Martínez et al, 2019), including government democracy (Okpe & Othman, 2021), public governance (S. Wu & Christensen, 2021), sustainable development (Okpe & Othman, 2021), government politics (S. A. Asongu & Nnanna, 2019), and Government (Lassou et al, 2019).…”
Section: The Network Between the Keyword "Corruption In Government Se...mentioning
confidence: 99%
“…In this respect, Rafaty [ 52 ] revealed that greater perceptions of corruption are highly and robustly associated with weaker climate policies. In the same vein, Cadoret and Padovano [ 53 ] and Mavragani et al [ 54 ] found that high levels of effective governance play a pivotal role in promoting and enhancing environmental performance (see also [ 55 , 56 ]). In this regard, it seems that the level of corruption is the common denominator of environmental studies, therefore making it one of the main examples of an institutional obstacle to the evolution of sustainable development.…”
Section: Literature Reviewmentioning
confidence: 99%